Fungal keratitis caused by Neurospora: a case report - Lu, Yao; Mo, Yijun; Weng, Yuesong; Li, Xiaohui (Frontiers in Medicine, 2024)
BackgroundWe report a rare case of fungal keratitis caused by Neurospora, a filamentous fungus that is widely distributed in soil and graminaceous plants.Case presentationA 40-year-old Mongoloid male patient came to our outpatient clinic with painful swelling of the left eye and redness, after being cut by a tree branch 1 week prior. After examination, the patient was diagnosed with a corneal ulcer of the left eye, and was given levofloxacin eye drops and levofloxacin ophthalmic gel. However, the patient did not respond to the treatment. After admission to the hospital, fungal mycelium was found in the corneal smear. To further identify the pathogen, a corneal scraping culture was used to extract fungal DNA and PCR amplification was performed using ITS universal primers, which was later sequenced and identified as Neurospora. We used fluconazole injections (0.2 g/100 mL) as eye drops to treat the patient once every hour, and itraconazole (200 mg) was administered orally once a day. After a few days, the patient’s condition improved.ConclusionTo the best of our knowledge, this is the first reported case of fungal keratitis caused by Neurospora in China. In this case, conventional topical and systemic treatment resulted in a favorable outcome. In patients with suspected fungal keratitis, medical treatment should be started urgently, and the treatment plan should be adjusted according to the subsequent experimental results and the patient’s condition.